Miliary Tuberculosis Induced Acute Liver Failure - Tayfur Toptas; Birkan Ilhan; Huseyin Bilgin; Elif Dincses; Osman Ozdogan; Isik Kaygusuz-Atagunduz; Zekaver Odabasi; Volkan Korten; Tulin Firatli-Tuglular (Case Reports in Infectious Diseases)
Hepatobiliary tuberculosis is uncommon even in endemic countries. It is associated with a high mortality and is even diagnosed early in the disease course. Acute liver failure (ALF) caused by tuberculosis bacilli has been reported in only a few reports. All previous cases have been diagnosed by postmortem examination. Time to antituberculosis treatment is very critical. In case of suggestive findings on clinical and radiologic examination, antituberculosis treatment should be initiated immediately. Drug use can be a challenge in patients with ALF. However, as long as the other possible causes of ALF can be excluded and hepatotoxic drugs were avoided during the early course of treatment, such a highly fatal presentation of tuberculosis can be treated safely. Here, we report a case of acute liver failure as a presentation of miliary tuberculosis. He was treated successfully with antituberculosis treatment.